Pseudomeningitis due to Pseudomonas aeruginosa in a paedriatic ward of a tertiary care centre: a glimpse on infection control measures - Sood, Anuradha; Gupta, Puneet Kumar; Thakur, Kamlesh; Chauhan, Smriti; Jaryal, Subhash Chand; Gautam, Piyush (International Journal of Infection Control, 2016)
Paediatric bacterial meningitis is a life threatening illness. We report a pseudo-outbreak of Pseudomonas aeruginosa meningitis in neonates from the neonatal intensive care unit (NICU) and paediatric ward of our 567 bed tertiary care hospital. The infection control team (ICT) investigated the cause of a sudden significant increase of Pseudomonas meningitis in neonates. A retrospective analysis of all the isolates from CSF and environmental sampling from NICU and paediatric ward was done. Direct culture of autoclaved rubber caps of glass vials as well as cetrimide and chlorhexidine solution yielded growth of P. aeruginosa, with an antibiogram similar to CSF isolates. Pseudo-infection not only burdens the work of health care providers but also has financial implications; hence every measure should be taken to prevent it.